2014
DOI: 10.1128/iai.01606-13
|View full text |Cite
|
Sign up to set email alerts
|

Host Response to Nontuberculous Mycobacterial Infections of Current Clinical Importance

Abstract: The nontuberculous mycobacteria are a large group of acid-fast bacteria that are very widely distributed in the environment. While Mycobacterium avium was once regarded as innocuous, its high frequency as a cause of disseminated disease in HIV-positive individuals illustrated its potential as a pathogen. Much more recently, there is growing evidence that the incidence of M. avium and related nontuberculous species is increasing in immunocompetent individuals. The same has been observed for M. abscessus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 86 publications
0
56
0
2
Order By: Relevance
“…The cure rate for chronic lung and disseminated infections due to NTM is dismal despite prolonged treatment with various multidrug regimens (6,7). Treatment of M. abscessus consists of macrolides, quinolones, amikacin, and other antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cure rate for chronic lung and disseminated infections due to NTM is dismal despite prolonged treatment with various multidrug regimens (6,7). Treatment of M. abscessus consists of macrolides, quinolones, amikacin, and other antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…RGM cause serious, lifethreatening chronic lung disease and are responsible for disseminated and often fatal infections (6,7). Infections are typically caused by contaminated materials and invasive procedures involving catheters, nonsterile surgical procedures, or injections and implantations of foreign bodies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been a significant increase in the incidence of nontuberculous mycobacterial (NTM) lung infections, including in cystic fibrosis patients, where M. avium subsp. hominissuis accounts for 72% of mycobacterial infections (2)(3)(4). Studies have also found an increase in NTM lung infections in middle-aged women with no known underlying conditions (5).…”
mentioning
confidence: 98%